Analysis of the use of tractors in different poles of agricultural development in Benin Republic - Zokpodo, Koessi Lié Barnabé; ATIDEGLA CAPO, Séraphin Cocou (My University, 2021)
The deep assessment of agricultural mechanization inside developing countries could help for local action-taking. This study investigates the use of tractors between the poles of agricultural development (PAD) in Benin Republic. Using a multi-stage random sampling procedure and a questionnaire, 203 tractor users were surveyed in 43 municipalities distributed across the seven PADs of the country. Kruskal-Wallis tests were carried out to compare the different poles of agricultural development based on the mechanization level and tractor performances. Student-Newman-Keuls tests were used to structure the means of these variables. The results show a significant variation (P < 0.05) of the mechanization level between the PADs. Apart PAD1, all the poles use greater than 60 % manual equipment. Animal-drawn is most implemented in the northern part of the country (PAD1; 2 and 3). The use of tractors is lower over the country, and the PAD2 and PAD3 are the most users. From PAD4 to PAD7, the combination of manual tillage with animal power or tractor is not well represented, indicating manual tillagebased agriculture in these poles. In general, 53.20% of the users do not have a tractor parking and the repair center is quasi-absent (97.54 %). PAD2; 4 and 3 are most disc plow users. Mechanical sowing is more observed in PAD2 and 7 and absent in PAD1; 3 and 4. Moreover, the harvester is present in PAD2; 4; 6, and 7. On average, the highest mechanized area was 134.56 ha from PAD3, whereas, the lowest, 12.00 ha was found in PAD7. PAD7 spends more on plowing (47670 FCFA) than the other poles. The mechanized plowing is most slower in PAD7 (3.53 h/ha) while much faster at the PAD2 (1.96 h/ha). These results could help decision-makers for accurate actions taking to advocate for agricultural mechanization sectors in the country based on the weakness of each pole of agricultural development.
Keywords: Machinery use; Tractor performances; Local development; Mechanization level; Benin